The Creation of Furniture Products from Rice Stubble - Somchai Seviset; Songwut Egwutvongsa (IntechOpen eBooks, 2021)
The objective of this research was to develop the transformation procedure of rice stubble in the dry season of Thailand. This would be significantly used for the creative building processes of furniture products for earning increased economic value for the people and the communities. Fiber was applied in the transformation procedure for the rice stubble, including the cementing of the formation procedure in the boiling and soaking methods. From the results from using both procedures in this research, it was found that knock-down furniture sheets had the ability to be formed as standard furniture products with JIS A 5908–1994 for the customer groups who had the most level of satisfaction to rice stubble furniture. Therefore, this resulted in a positive result affecting the reduction of the ratio of burning of rice stubble in terms of preparing the area for planting in the next season on a large scale, including decreasing the occurrence of the PM. 2.5 problem in Thailand in every winter season. As a result, this research could be considered as another choice as a proposal to present the solution guidelines for solving the PM. 2.5 problem sustainably.
Keywords: Architectural and Urban Studies